The Role of Vitamin C and Thyroxine Hormone (T4) on the Growth of Asian Redtail Catfish (Hemibagrus nemurus) in the Recirculation System - Anang Widarsa; Usman M Tang; Henni Syawal (Faculty of Fisheries and Marine, Universitas Riau, 2024)
This research was conducted in January-July 2021 at the Marine Science Technology Biology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The purpose of the study was to see the effect of a combination dose of vitamin C and thyroxine hormone (T4) on the growth rate and survival of bream reared in a recirculation system. The method used was an experimental method using a factorial complete randomized design (CRD) with 2 factors and 3 replicates. The first factor is vitamin C, while the second factor is the dose of tyrrhosine hormone (T4) given during maintenance. The doses of vitamin C used in this study were; 0 mg/kg (V0), 500 mg/kg (V1), 1000 mg/kg (V2). Doses of thyroxine hormone (T4) used were doses; 0 mg/kg (H0), 4 mg/kg (H1), 6 mg/kg (H2), 8 mg/kg (H3). The Asian redtail catfish used were 8-10 cm in size and reared in a round container made of PE plastic with a diameter of 56 cm and a height of 48 cm, totaling 36 units. The pellets used were Hi-Provite 781-2 with 31% protein, with feeding done 3 times a day ad satation. The results showed that the addition of vitamin C and thyroxine hormone influenced the growth of Asian redtail catfish reared in the recirculation system. The combination of vitamin C 1000 mg/kg and thyroxine hormone 8 mg/kg feed gives the highest growth and survival, seen from the absolute weight growth rate of 12.97 g, specific growth rate of 1.93 g/day, and 95% survival. Water quality during rearing was favorable for the growth of Asian redtail catfish, with temperature ranging from 28-30oC, pH 6.5-7.0, and DO 4.2-5.95 ppm.